(untitled) (Swiss Medical Weekly, 2017)
The topic of interprofessional collaboration (IPC) between healthcare professionals has been widely discussed in recent years. Whereas the growing calls for more and better IPC can scarcely be ignored and a broad range of definitions and normative concepts have been proposed, it remains unclear what IPC actually means for practising professionals. This exploratory survey investigated the various ways in which successful IPC is understood in practice. As a main finding of the study, we were able to identify three distinct modes of collaboration between different professions in health care. Moreover, we provide evidence that whether and how IPC occurs strongly depends on the care contexts or settings in which these health professionals work. Explicit acknowledgement of and attention to these findings could improve the impact of initiatives to foster IPC.